FREE TRADE IN EURASIA? OR IS HOME WHERE THE HEART IS? - Waalkens, Jan; Samplonius, Shilpa (European Scientific Journal, ESJ, 2014)
Free trade benefits us all and is firmly guarded by the WTO. In earlier research we showed that complaining at the WTO is not always induced by objective facts. We argue that if this is actually the case, trade is not sustainable as it should be, but disruptive instead. It implies that sub optimality is introduced, distorting the beneficial effect of free trade known as in the theory of comparative advantage. In this paper we look at the complaining behaviour on the Eurasian continent and we try to distil driving forces. We are particularly interested in the role of the European community, one of the major complainants. Can we explain this behaviour in terms of home bias, as we found for several other nations, or is this complaining related to objective facts which are subject of international treaty’s such as airplane safety? In our earlier exploratory research we worked on data of 28 countries which we analysed using correlation and stepwise regression, finding interesting results. We actually distilled a trend involving home bias. We again pose the question if Eurasian complaining is actually about for instance airplane safety or do also Eurasian countries use treaty’s like this to steer away from competition? Is this leading to disruptive trade or the opposite, making trade more free and sustainable? We use statistical analysis and report on a number of incidents, and eventually focus on the role of Foreign Direct Investment in the subset of 28 countries versus Eurasia. We explain why results between the subsets differ to a considerable extent and show convincing examples of home bias induced policy.